2012
DOI: 10.1371/journal.pone.0029574
|View full text |Cite
|
Sign up to set email alerts
|

Fishing the Molecular Bases of Treacher Collins Syndrome

Abstract: Treacher Collins syndrome (TCS) is an autosomal dominant disorder of craniofacial development, and mutations in the TCOF1 gene are responsible for over 90% of TCS cases. The knowledge about the molecular mechanisms responsible for this syndrome is relatively scant, probably due to the difficulty of reproducing the pathology in experimental animals. Zebrafish is an emerging model for human disease studies, and we therefore assessed it as a model for studying TCS. We identified in silico the putative zebrafish T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…Indeed, our results showed that CNBP depletion leads to tbx2 down-regulation and, moreover, to p21 up-regulation trough a p53-independent pathway. On the other hand, cnbp was reported as a gene likely involved in Treacher Collins Syndrome (TCS, OMIM #154500) [33]. TCS is an autosomal dominant craniofacial malformation caused by mutations in the Treacher Collins-Franceschetti syndrome 1 gene (TCOF1, OMIM*606847).…”
Section: Identification Of Novel Cnbp Gene Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, our results showed that CNBP depletion leads to tbx2 down-regulation and, moreover, to p21 up-regulation trough a p53-independent pathway. On the other hand, cnbp was reported as a gene likely involved in Treacher Collins Syndrome (TCS, OMIM #154500) [33]. TCS is an autosomal dominant craniofacial malformation caused by mutations in the Treacher Collins-Franceschetti syndrome 1 gene (TCOF1, OMIM*606847).…”
Section: Identification Of Novel Cnbp Gene Targetsmentioning
confidence: 99%
“…TCS is an autosomal dominant craniofacial malformation caused by mutations in the Treacher Collins-Franceschetti syndrome 1 gene (TCOF1, OMIM*606847). In zebrafish, tcof1 loss-of-function represses tbx2 expression while up-regulates ndrg1 (N-myc downregulated gene 1) and p21 expressions [33]. Since Tbx2 represses the expression of ndrg1 acting as a co-repressor through recruitment of EGR1 [34], the role of CNBP as tbx2 up-regulator may explain not only the increase of p21 expression detected in cnbp-and tcof1-morphants but also the increase of ndrg1 expression detected in TCS-like zebrafish embryos.…”
Section: Identification Of Novel Cnbp Gene Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent studies, the pathogenesis of TCS is also related to p53: mutation in one allele of the TCOF1 gene induces cellular stress that activates p53, which leads to death and abnormal differentiation of neuroepithelial cells [58]. An animal model of TCS with a TCOF1-equivalent gene has al- [59]. Further use of this model should demonstrate the exact role of TCOF1 in the formation of TCS.…”
Section: Pierre Robin Sequencementioning
confidence: 99%
“…The first syndrome-related gene, TCOF1, was only identified in 1996 6 . Mutations in this gene are responsible for about 90% of TCS cases 7 . Over 130 pathogenic mutations have already been identified in TCOF1 gene 5 .…”
Section: Introductionmentioning
confidence: 99%